Analisis Usaha Budidaya Ikan Lele (Clarias sp) Pada Kelompok Budidaya di Kampung Buana Bakti Kecamatan Kerinci Kanan Kabupaten Siak - Inayah Ramadhani; Darwis; Hazmi Arief (Jurusan Sosial Ekonomi Perikanan, 2021)
This research was conducted in March 2020 at Buana Bakti Village, Kerinci kanan Sub-district Siak district. The location of this study was determined deliberately (purposive sampling) with the consideration that Buana Bakti Village has a good enough potential to carry out catfish (Clarias sp) farming activities. The respondents in this study were taken by census. The catfish rearing cultivation business in Buana Bakti Village, Kerinci kanan Sub-district Siak regency has been established since 2017. The total investment is IDR 71.113,000, which consists of a fixed capital of IDR 41.006,000, and working capital of IDR 30.107,000.The total revenue received by the cultivator group in conducting the catfish enlargement business is IDR 42.500,000, and revenue per year of IDR 170.000,000, meanwhileThe income earned by the group per period is IDR 10.379.000, and the income per year is IDR 41.519.000. Based on the calculation of the investment criteria, it was found that the RCR value of the Catfish Cultivator group in Buana Bakti Village was 1,32. Meanwhile, the ROI value for the cultivator group was 14,16%. PPC value for catfish rearing business is 1,64 period.